(untitled) (El-Wahat Journal for Research and Studies, 2025)
Organic Coherence Is One Of The Most Important Textual Criteria In Text Linguistics, As It Focuses On The Underlying Structure Of Connective Devise Visible In The Text, As A Result, It Investigates The Semantic Relationships That Enable The Reader To Grasp The Content Of The Text, Understaw It, And Interpret It Based On Mechanisms That That Text Facilitate This Among The Most Prominent Of These Mechanisms, We Find The Topic Of Discourse Persuasion , Background Knowledge And Context, To Represent The Uniquenesss Of Coherence, We Chose The Ancient Moroccan Literary Poems, Specifically Selecting Mawlidiyat Text As A Cultural Model That Reflects The Maturity Of Artistic Ability In Shaping The Mawlidiyat Discousse This Led Us To Examine It From Linguistic And Descriptive Perspective To Identify The Elements Of Cohesion And Organic Cohesence Within The Mawlidiyat And Assess Their Alignment With The Semantic Structures In Its Poetry. Key Words : Text Linguistics ,Harmony,Textual,The Speech, Mawlidiyat.